INTERAKSI KOTA SIBOLGA DENGAN KOTA PANDAN - , Melanthon Sihontang ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is motivated by the relocation of the capital of Central Tapanuli Regency from Sibolga City to Pandan City. The relocation was done to accelerate the development of Central Tapanuli Regency. The distance between Pandan City and Sibolga City is only 10 kilometers away highly affects the interaction between the two cities. The objectives of this research are : (1) to describe the interaction occured